1998
DOI: 10.1164/ajrccm.157.4.9704036
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and Race/Ethnicity in the United States

Abstract: Despite the long-standing observation that tuberculosis (TB) case rates are higher among racial and ethnic minorities than whites in the United States (U.S.), the proportion of this increased risk attributable to socioeconomic status (SES) has not been determined. Values for six SES indicators (crowding, income, poverty, public assistance, unemployment, and education) were assigned to U.S. TB cases reported from 1987-1993 by ZIP code- and demographic-specific matching to 1990 U.S. Census data. TB risk between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
119
2
14

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(149 citation statements)
references
References 10 publications
14
119
2
14
Order By: Relevance
“…In agreement with the only previous zip code-level study of TB among US minorities, 6 we generally found an increase in exposure to risk factors, contact with immigrants, isolation, and density as we moved from no TB to very high TB zip codes. However, these gradients varied by racial/ethnic group.…”
Section: Descriptive Statisticssupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with the only previous zip code-level study of TB among US minorities, 6 we generally found an increase in exposure to risk factors, contact with immigrants, isolation, and density as we moved from no TB to very high TB zip codes. However, these gradients varied by racial/ethnic group.…”
Section: Descriptive Statisticssupporting
confidence: 91%
“…Considerable historical and contemporary evidence indicates that TB is positively associated with low socioeconomic status (e.g., poverty) 5,6,8,[15][16][17] and substandard housing conditions (e.g., crowding and dilapidation). [18][19][20] Residential segregation may have an indirect effect on TB trans- [1985][1986][1987][1988][1989][1990][1991][1992] Note.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Os segmentos populacionais socioeconomicamente menos favorecidos são aqueles que tendem a apresentar maior vulnerabilidade à tuberculose (Cantwell et al, 1998;Elen-der et al, 1998). Os resultados obtidos a partir da análise do banco de dados do PCT-RO estão de acordo com a literatura, no sentido de apontar os grupos indígenas como mais vulneráveis à tuberculose.…”
Section: Discussão E Conclusõesunclassified
“…23,24 Genetic differences undoubtedly have a role in susceptibility to active TB infection, but ascription of the influence of race or ethnicity to susceptibility to TB remains, at best, controversial, 25 especially as other correlates such as socioeconomic status can also explain why some populations have higher incidence of infection. 26,27 Yet social inequality in disease is only partially explained by the classic behavioural dimension of health risk exposure. Structural conditions can perpetrate violence against distinct populations by preventing them from meeting their most basic needs.…”
mentioning
confidence: 99%